2018
DOI: 10.2298/vsp160419208m
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between adiposity parameters and C-reactive protein values in overweight and obese women

Abstract: Background/Aim. Overweight/obesity has become important health problem in developed countries. It may be related to a presence of low-grade inflammation in white adipose tissue. The aim of this study was to investigate the levels of inflammatory marker C-reactive protein (CRP) and its relation to anthropometric parameters in overweight and obese females. Methods. This study included 200 apparently healthy, overweight and obese women (18-45 years). Their standard and alternative anthropometric parameters [body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…The BFP was associated with increased serum CRP levels. These results are found in several studies in which an increase in body fat in apparently healthy women aged 18 to 60 is associated with increased CRP concentrations (Pannacciulli et al, 2001) and an increase in BMI (Cesari et al, 2005;Mraovic et al, 2018). In addition, we found that menopausal status modified the relationship between CRP and FMI.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The BFP was associated with increased serum CRP levels. These results are found in several studies in which an increase in body fat in apparently healthy women aged 18 to 60 is associated with increased CRP concentrations (Pannacciulli et al, 2001) and an increase in BMI (Cesari et al, 2005;Mraovic et al, 2018). In addition, we found that menopausal status modified the relationship between CRP and FMI.…”
Section: Discussionsupporting
confidence: 88%
“…Adipose tissue is a highly active metabolic complex endocrine tissue that is fundamental to inflammation (Fuentes et al, 2013; Izaola, 2015). Mraovic et al (2018) proposed that the mechanism for the induction of inflammation in obesity is the secretory activity of adipose tissue, which is the site of production of proinflammatory cytokines, such as tumor necrosis factor-alpha (TNF-α) and interleukin 6 (IL-6). In addition to adiposity, age and some diseases, such as cancer, are well-recognized contributing factors to human cytokine imbalance (Cesari et al, 2005; Rea et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the light of the fact that obesity has become the epidemic health threatening condition, its effects on physical health were extensively studied and well-documented [5][6][7]16 . However, the relationship between the psychiatric and/or psychological factors and etiology and obesity treatment is complicated and not well-known.…”
Section: Discussionmentioning
confidence: 99%
“…Empiric and scientific data confirmed its clear association with plethora of medical conditions (metabolic syndrome, type 2 diabetes, ischemic heart disease, stroke, inflammation, apnea, certain carcinoma, etc.) 1,[5][6][7] and decreased quality of life 8,9 . If the current trend of increased morbidity and mortality due to obesity continues, the life expectancy in future could decrease for the first time in modern history 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is a major public health problem in the world, affecting people in developed and developing countries. 2,8,9 In 2016, 39% of adults aged 18 years and above (39% of men and 40% of women) were overweight; overall, approximately 13% of the world's adult population (11% of men and 15% of women) were obese. 10 Obesity is associated with metabolic syndrome, development of type II diabetes, 11 and coronary heart disease.…”
Section: Introductionmentioning
confidence: 99%